Longitudinal emotional process among adolescent soccer player in intensive training centre - Saby, Y.; Pupier, Y.; Guillet-Descas, E.; Nicolas, M.; Martinent, G. (Journal of Sports Sciences, 2020)
Grounded in Lazarus`s (1999) cognitive motivational relational theory of emotions, this study aimed to explore longitudinal relationships between appraisals, everyday emotions related to the competitive environment and emotional regulation strategies during a competitive season. Forty adolescent soccer players (Mage = 15.8) involved in an intensive training centre from a professional club voluntarily participated to the study. A series of hierarchical linear modelling analyses were conducted upon the 9 measurement times to: (a) examine the relationships between appraisals (threat, challenge, loss), pleasant (happiness, excitement) and unpleasant (anxiety, dejection, anger) emotions, and emotional regulation strategies (adaptive and less adaptive); and (b) ascertain whether the relationships between appraisals and emotions were mediated by emotion regulation strategies. The results of the random coefficient regression models showed: (a) positive relationships between challenge appraisal, adaptive emotion regulation, and pleasant emotions as well as between threat and loss appraisals, less adaptive emotion regulation and unpleasant emotions; and (b) mediating effects of emotional regulation strategies in the appraisals - emotions relationships. As a whole, this study furthered knowledge base about the competitive environment in showing that appraisals, emotion regulation and emotions are intertwined psychological constructs in a dynamic relationship allowing athletes to continuously adjust to their constantly changing everyday demands.